Mirʼāt al-quds (Mirror of holiness) : a life of Christ for Emperor Akbar : a commentary on Father Jerome Xavier's text and the miniatures of Cleveland Museum of Art, Acc. numbers 2005.145 - Carvalho, Pedro de Moura. (Muqarnas, Supplements, 2011)
Emperor Akbar's exceptional interest in Christianity is reflected in many ways. Among these was his commissioning in 1602 of a Life of Christ from his guest, the Jesuit priest Jerome Xavier, thus marking a singular moment in the relations between one of the greatest Muslim rulers and Catholicism. This fascinating text-translated into English for the first time-draws mostly on Biblical and apocryphal sources, but also reveals that in order not to antagonize his Muslim hosts, Father Jerome occasionally made concessions in his work. Of the three illustrated copies, the one used in this study and now in the Cleveland Museum of Art is the most important. Its twenty-seven high-quality miniatures were inspired by the text itself, resulting in unique interpretations of episodes that often do not find parallels in a European context.